Paraquat and glyphosate action on purple nutsedge (Cyperus rotundus L.) in Olive Orchards - B, Hajjaj; A, El Oualkadi (International Journal of Environment, Agriculture and Biotechnology, 2019)
Abstract: A weed control trial was conducted in order to investigate the effect of two herbicides, paraquat and glyphosate, on Cyperus rotundus infestation in olive orchards. Treatments consist on two glyphosate rates of application and two paraquat rates of application. The experimental design was Randomized Complete Block Design (RCBD) with three replications. Each block contained five elementary plots, four plots of which were treated with the herbicides and the untreated plots serving as control. Observations were carried out at 30 and 90 days after application of herbicides. Results showed that treatment with glyphosate at 1080 g/ha and Paraquat at 400 g/ha recorded 100% of visual efficacy rating on C. rotundus at 30 days after treatment. At 90 days after treatment, glyphosate at 1080 g/ha showed the best efficacy recording 80% of visual efficacy rating on C. rotundus. However, paraquat at 800 g/ha showed weak control of C. rotundus recording only 50%. Glyphosate at 1080 g/ha recorded 78.6% of C. rotundus dry biomass reduction at 90 days after treatments. Paraquat at 400 g/ha, paraquat at 800 g/ha and glyphosate at 540 g/ha recorded weak efficacy varying from 34.7% to 53.5 % of C. rotundus dry biomass reduction at 90 days after treatments. Glyphosate at 1080 g/ha could be recommended to olive farmers when C. rotundus infestation is dominant.